NEAP/DUSP26 suppresses receptor tyrosine kinases and regulates neuronal development in zebrafish - Chi-Hwa Yang (Nature Portfolio, 2017)
Abstract Expression of neuroendocrine-associated phosphatase (NEAP, also named as dual specificity phosphatase 26, [DUSP26]) is restricted to neuroendocrine tissues. We found that NEAP, but not its phosphatase-defective mutant, suppressed nerve growth factor (NGF) receptor TrkA and fibroblast growth factor receptor 1 (FGFR1) activation in PC12 cells upon NGF stimulation. Conversely, suppressing NEAP expression by RNA interference enhanced TrkA and FGFR1 phosphorylation. NEAP was capable of de-phosphorylating TrkA and FGFR1 directly in vitro. NEAP-orthologous gene existed in zebrafish. Morpholino (MO) suppression of NEAP in zebrafish resulted in hyper-phosphorylation of TrkA and FGFR1 as well as abnormal body postures and small eyes. Differentiation of retina in zebrafishes with NEAP MO treatment was severely defective, so were cranial motor neurons. Taken together, our data indicated that NEAP/DUSP26 have a critical role in regulating TrkA and FGFR1 signaling as well as proper development of retina and neuronal system in zebrafish.